Heavy metals content in edible mushrooms: A systematic review, meta-analysis and health risk assessment. (March 2021) - Dowlati, Mohsen; Sobhi, Hamid Reza; Esrafili, Ali; FarzadKia, Mahdi; Yeganeh, Mojtaba
Abstract: Background: There has been a sharp rise in the rate of consumption of edible mushrooms all over the world. Although mushrooms are regarded as valuable healthy foodstuff, they can be a source of possibly toxic heavy metals which could adversely affect health. Scope and approach: A systematic review and meta-analysis search on the concentration of toxic heavy metals in edible mushrooms was conducted within the period from Jan 1, 1970 to Jun 21, 2020. To finding the relevant articles, we used the scientific databases including PubMed, Web of Science, and Scopus. Furthermore, the associated human health risk was assessed by calculating the target hazard quotient (THQ) aided by the Monte Carlo (MCS) model. Key findings and conclusions: Of 59 retained articles subjected to the systematic review and meta-analysis, the toxic heavy metals concentrations in the edible mushrooms were ranked in the following order: Fe (204.5716 mg/kg) > Zn (154.6076 mg/kg) > Cu (32.1996 mg/kg) > Mn (25.4007 mg/kg) > Ni (10.4375 mg/kg) > Cr (4.934 mg/kg) > Pb (2.4844 mg/kg) > Cd (1.3925 mg/kg). Furthermore, the concentrations of heavy metals in some parts of edible mushrooms including Cap and Stipe were assessed and the findings revealed that Pb, Cu, Fe, Cd, Cr and Zn are readily accumulated within the Caps in larger amounts, whilst Mn and Ni tend to build up more in the Stipes. Finally, due to the ingestion of heavy metals, the edible mushrooms consumers such as adults and children in some countries could be subjected to significant non-carcinogenic risks. Graphical abstract: Image 1 Highlights: First comprehensive systematic review on the quantity of Heavy Metals in Edible Mushrooms. 59 articles reports underwent the meta-analysis. Rank in order of mean concentration was as follows: Fe > Zn > Cu > Mn > Ni > Cr > Pb > Cd. Non-carcinogenic risks due to heavy metals ingesting in Edible Mushrooms.